2014
DOI: 10.1038/srep07130
|View full text |Cite
|
Sign up to set email alerts
|

DHA-PC and PSD-95 decrease after loss of synaptophysin and before neuronal loss in patients with Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease that is characterized by senile plaques, neurofibrillary tangles, synaptic disruption, and neuronal loss. Several studies have demonstrated decreases of docosahexaenoic acid-containing phosphatidylcholines (DHA-PCs) in the AD brain. In this study, we used matrix-assisted laser desorption/ionization imaging mass spectrometry in postmortem AD brain to show that PC molecular species containing stearate and DHA, namely PC(18:0/22:6), was selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 52 publications
6
71
0
1
Order By: Relevance
“…Post-mortem hippocampus specimens were prepared from 8 AD patients and 9 non-AD subjects in the Choju Medical Institute as previously described48. The brain was removed at autopsy, weighed, cut mid-sagittally, and examined for vascular and the other macroscopically detectable lesions.…”
Section: Methodsmentioning
confidence: 99%
“…Post-mortem hippocampus specimens were prepared from 8 AD patients and 9 non-AD subjects in the Choju Medical Institute as previously described48. The brain was removed at autopsy, weighed, cut mid-sagittally, and examined for vascular and the other macroscopically detectable lesions.…”
Section: Methodsmentioning
confidence: 99%
“…72,73 Interestingly, decreased DHA distribution in AD patient brains correlates with synaptic loss rather than amyloid beta (Aβ) deposition. 74 In addition, DHA or SPMs promote phagocytosis of Aβ42 by microglia 75 and modulate microglia number and activation in vivo. 76 Whether SPMs play a role in the protective activity of long chain omega-3 PUFA in mood and cognitive disorders associated to neuroinflammation remains to be established.…”
Section: Dietary Omega-3 Pufa Regulate Neuroinflammation and Ecbs: Romentioning
confidence: 99%
“…Thus, blueberry juice significantly improved word list recall and paired associate learning in older men and women with agerelated memory decline that consumed it, relative to baseline, with paired associate learning also significantly improved relative to placebo controls. 97 A recent study 98 that measured similar cognitive tasks as those in the rodent studies, showed that freezedried blueberries (24 g/day, equivalent to one cup of fresh blueberries) for 90 days improved two measures of executive function in older adults (ages [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Participants in the blueberry group showed significantly fewer repetition errors in the California Verbal Learning test as well as reduced switch cost on a taskswitching test across study visits, relative to controls who consumed placebo powder.…”
Section: Dietary Interventions With Polyphenolic-rich Foods Can Impromentioning
confidence: 99%
“…injection of mod2B (n = 4) significantly prolonged the lifespan (log-rank test) compared with the PBS-treated control. IMS is a powerful tool that can be used to detect many biomolecules and biological events at the same time, especially for qualitative lipid analysis (14,16), although it is an invasive technique. Therefore, IMS is also considered useful for monitoring therapy of animal models with neurodegenerative diseases including lipidosis and gangliosidosis.…”
Section: 9mentioning
confidence: 99%